An analysis of ideational foundations of Morocco's integration into ECOWAS - Suleiman, Muhammad Reza; Slighoua, Mounia; Haddad, Abderrahmane (Frontiers in Political Science, 2024)
This article examines the impact of ideational elements on state efforts to achieve regional integration, with a specific focus on Morocco's pursuit of membership in the Economic Community of West African States (ECOWAS). This study investigates how shared cultural heritage, historical narratives, and common views on principles such as free trade and security partnerships foster a sense of collective identity among states, thereby promoting deeper cooperation and integration within regions. However, conflicting ideologies can create obstacles to meaningful integration by breeding distrust and friction among participating states. This study argues that constructivism provides valuable insights into regional integration processes by emphasizing the importance of shared norms, identities, and social interactions among states. The analysis reveals that Morocco's aspiration to align with the interests of other African states in ECOWAS and promote economic integration serves as the ideological basis for its pursuit of ECOWAS membership, viewing it as a symbol of African resurgence and a means to strengthen its regional position. Although Morocco's history, laws, society, and politics align with ECOWAS norms, the absence of provisions for new members in the ECOWAS Treaty presents a hurdle for Moroccan accession. Nevertheless, this article suggests that the ECOWAS Authority of the Heads of State and Government could potentially address this issue by establishing a supplementary protocol to admit Morocco, underscoring the significance of ideological factors in shaping regional integration processes and institutions.